Investigating Student Perceptions of Vocabulary and Learning in Middle School Science - Concannon, Jim; Brown, Patrick (Advances in Social Sciences Research Journal, 2014)
Science courses are all too often taught as a litany of facts leading many students to focus on rote memorization of terminologies instead of developing deep conceptual understanding (Groves, 1995). The frequent use of a textbook can contribute to the problem. The purpose of this teacher classroom research study was to investigate the vocabulary demands and students’ perceptions of instructional strategies in an 8th grade physical science class. The findings indicate that 21 formal science vocabulary terms were presented for 17 relevant pages of the textbook. Students’ perceived “expanding vocabulary” and discussing examples of items as the most helpful instructional strategies for developing understanding. Students believed the pre-test of vocabulary content and reading and discussing vocabulary passages from the textbook at the onset of instruction were the least helpful instructional strategies. The results of this study provide a better understanding of the types of instructional strategies that students’ believe encourage vocabulary learning. Keywords: Vocabulary Teaching, Action Research, Middle School Science